Perhitungan Poros, Puli Dan Sabuk – V Pada Kompresor Merk Shark Lzpm-5114 - Iwan Nugraha Gusniar; Bayu Nugroho Putra Santoso (Jurnal Ilmiah Wahana Pendidikan, 2023)
In this modern era, technology is developing very rapidly, so that higher education programs are developed as maintenance, research and development centers. The task of machine elements is a good exercise for students so they can apply the knowledge they have acquired in the form of an analysis of an equipment. Compressor engines generally use electric motors, gasoline engines, or diesel engines as their driving force. The compressor also transmits power from one shaft to another through pulleys that rotate at the same or different speeds which is transmitted through a V-belt that is wound on the compressor pulley which will move back and forth on the piston/piston. For example, a compressor in a workshop is used to fill air in car or motorcycle tires. Compressors are also used to clean dirty engine parts and other benefits that are often encountered daily.